The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1109/tuffc.2012.2309
|View full text |Cite
|
Sign up to set email alerts
|

Time-domain calculation of spectral centroid from backscattered ultrasound signals

Abstract: Spectral centroid estimation from backscattered ultrasound RF signals is the preliminary step for quantitative ultrasound analysis in many medical applications. The traditional approach of estimating the spectral centroid in the frequency domain takes a long time because discrete Fourier transform (DFT) processing for each RF segment is required. To avoid this, we propose time-domain methods to estimate the spectral centroid in this paper. First, we derive the continuous-time-domain equations for the spectral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…In many of the simulation studies for attenuation estimation, a single scatterer size and an SND greater than 10 per mm is often used (Kim and Varghese, 2008, 2007; Kim et al, 2008; Kim, H. and Heo, S.W., 2012; Labyed and Bigelow, 2011; Nam et al, 2011a; Omari et al, 2011, 2013). This is done to yield Rayleigh scattering statistics.…”
Section: Introductionmentioning
confidence: 99%
“…In many of the simulation studies for attenuation estimation, a single scatterer size and an SND greater than 10 per mm is often used (Kim and Varghese, 2008, 2007; Kim et al, 2008; Kim, H. and Heo, S.W., 2012; Labyed and Bigelow, 2011; Nam et al, 2011a; Omari et al, 2011, 2013). This is done to yield Rayleigh scattering statistics.…”
Section: Introductionmentioning
confidence: 99%
“…attenuation estimation performances, including computational time, estimation accuracy and precision, of the FFT-based spectral-domain method and the time-domain method using an optimized weighting function were previously reported by the authors in [13]. In summary, simulation results using numerical phantoms showed that the time-domain method was approximately 4.4 times faster on average compared with the FFT-based method for various block sizes (from 3 mm × 3 mm to 6 mm × 6 mm) and overlap ratios (from 50 to 90%).…”
Section: B Comparison Of Estimation Performances Using the Optimizedmentioning
confidence: 86%
“…In a previous work by the authors in [13], the calculation of the spectral centroid in the discrete time domain using Parseval's theorem is derived as follows: …”
Section: Review Of the Time-domain Relationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The spectral centroid is one of physical parameters in the timbre which is an attribute of subjective experience for a sound stimulus [8]. Timbre can distinguish two sounds of equal loudness and tone, so the spectral centroid is more for voice signal recognition [9][10][11]. This paper introduces spectral centroid to electromagnetic signal processing because we found that spectral centroid can describe the special characteristics of video leaking signal.…”
Section: Introductionmentioning
confidence: 99%